ANALISIS KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN - Tuti Sulastri (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2016)
Increasing competition,many universities that involved in fulfilling the needs and desires of students cause every collag e put the orientation on satisfaction of the students as a primary goal so many parties concern with the satisfaction and dissatisfaction of students in collage. This research aims to determine the response of students to performance of the lecture of Unisma and determine the factors of service (performance) that affect satisfaction or dissatisfaction of the student of Unisma. The research method that is used is descriptive analysis by using the level of expectation and performance that is presented using Cartesian diagram. The general performance of lecturer is not yet fully comply with the expectation of the students because the of compliance 97,33% smaller than 100%. Students rate the performance which is the highest is (4,15) on personal authority as lecturer and the lowest (3,38) on the diversity of measurement way in learning outcomes. The highest of compliance level is 102,52% on “personal authority as lecturer”, and from whereas the order of compliance from the highest to the lowest level is the aspect of personality competence (99,11%), social competence (99,06%), professional competence (96,52%), dan pedagogic competence (95,91%).